Application of biological early warning systems: implementing a prospective approach to water quality monitoring - Krainiukov , O. M.; Shchokina, M.M. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 2025)
Purpose. To review international experience in the development and improvement of biological early warning systems.Methodology. To assess the potential for improving existing biological early warning systems for continuous monitoring of water quality in different water categories.Results. Behavioral responses have been used for decades as tools for testing aquatic toxicity, but have received much less attention than studies assessing lethality, development, or reproduction. With the improvement of visual and non-visual assessment tools and the increasing knowledge of the importance of behavior for health and fitness, interest in behavioral analysis has increased in recent years. However, to our knowledge, no quantitative evaluation of available methods for testing toxicity in organisms has ever been conducted, and it is unclear whether behavioral studies are a valuable addition to aquatic monitoring. This literature review suggests that behavioral assays are relatively rapid and sensitive and therefore deserve further attention as tools for assessing the toxicological effects of aquatic pollutants. We believe that research aimed at developing and optimizing behavioral assays could prove extremely useful to the field of toxicology, but future work should be directed at determining which specific behavioral patterns are most sensitive to different classes of pollutants, and at understanding the significance of changes in discrete behaviors for health and fitness impacts.Conclusions. Biological Early Warning Systems (BEWS) rely largely on behavioral responses, with some also assessing other parameters, such as effects on algal chlorophyll fluorescence, at peak pollution levels, from which threshold values are derived. Behavioral changes are superior to mortality rates and other sublethal responses because they bridge the gap between individual and population relevance and are indicators of significant impacts of chemical contamination on a population before more serious consequences (i.e., population declines) occur.